Metallic chains/chains of metals - Springborg, Michael (Handbook of metal physics., 2007)
The present book describes a large variety of different types of chain systems (nanowires), including shorter chains that are artificially produced for instance in break-junction experiments, chains synthesized as guests inside the channels of a host crystal, crystalline chain compounds, organic polymers (synthetic metals), and charge-transfer salts, thus covering an unusual wealth of systems. Both experimental and theoretical studies are discussed. Particular emphasis is put on illustrating the special phenomena that occur in such quasi-one-dimensional systems, and how theoretical and experimental efforts have been used in identifying those properties that are specific for truly one-dimensional systems from those of quasi-one-dimensional systems. Moreover, it is shown that metallic chains can be found in a large range of systems, but also that chains of metals not always are metallic. Gives a unifying description of very many different phenomena and systems High-Tc superconductors, conjugated polymers, gold nanowires, carbon nanotubes, chain compounds, and charge-transfer salts are all treated in one volume Illustrates the very broad range of quasi-one-dimensional systems.